Parental perceptions of barriers to mental health services for young people. Issue 2 (20th October 2015) - Iskra, Wendy; Deane, Frank P.; Wahlin, Tim; Davis, Esther L.
Abstract: Aim: This study explores a range of barriers that parents encountered in accessing mental health services. The study also explored whether parents experienced similar barriers to accessing services in 2003 and 2013. Methods: One hundred and thirty‐four parents of young people attending an initial assessment at a Child and Adolescent Mental Health Service (CAMHS) orheadspace centre completed a questionnaire assessing 10 general barriers to care. These data were compared to those collected from 129 participants at CAMHS in 2003. Results: The ranking of barriers to mental health care for their children was similar for both survey years, with 'wait time being too long' and 'help being too expensive' the two highest ranked barriers. Cost factors were related to not knowing that the services did not charge fees and having to take time off work to attend appointments. Multiple referral steps and uncertain wait times were the main concerns regarding wait times. The overall strength with which barriers were endorsed remained relatively low; however, at least 40% of the sample agreed they had experienced four of the barriers in both years. Conclusions: Despite relatively low endorsement of barriers, there are substantial proportions of parents who experienced some barriers to services, and services should continue working to reduce them to facilitate timely access. There is a particular need for more service‐related information to clarify that public sector mental health services do not charge fees. Methods such as rapid initial assessment and actively managing wait lists may go some way to reducing perceived wait time barriers.